Jamaica : Staff Report for the 2002 Article IV Consultation and a New Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2002)
This paper focuses on the 2002 Article IV Consultation and a New Staff-Monitored Program (SMP) for Jamaica. In June 2000, the Jamaican authorities undertook an SMP for FY2000/01-2001/02 designed to tackle the heavy public sector burden and restore economic growth. To build on the progress achieved so far, the government has requested a new SMP for FY2002/03. The objectives of the program are to consolidate gains in macroeconomic stabilization and adjustment achieved to date and to lay the foundations for sustainable, strong economic growth that would further reduce poverty.